Characteristics of Whey from Dangke Cow Milk Waste with Coagulant Lime Extract - Bandrio, Dhany; Windyasmara, Ludfia (Jurnal Biologi Tropis, 2025)
Local dairy products are one of Indonesia's traditional food assets that can still be developed in terms of economy, culture, and nutritional value. This coagulation process is usually carried out by adding natural coagulants such as acetic acid or papaya latex, and in this study lime extract acts as a differentiator that will induce milk protein to coagulate into a liquid called whey and a solid mass (curd) called dangke. The materials used include 500ml of cow's milk, and 15g of coarse salt. The experimental method used using a completely randomized design (CRD) is a research methodology used with P0 treatment without the addition of lime extract, P1 0.5ml, P2 1ml, P3 1.5ml, and P4 2ml. The dangke cheese treatment was determined randomly, and each treatment had 3 replications so that there were 15 experimental units. The study found that although soluble protein had no significant effect, pH, total acid, and viscosity of dangke whey of cow's milk produced with a coagulant made from lime extract. have a very significant effect. The use of whey can reduce the possibility of environmental pollution by reducing liquid waste from the dairy processing sector, such as dangke.